2020
DOI: 10.1111/raq.12420
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity–Ecosystem Functioning (BEF) approach to further understanding aquaculture–environment interactions with application to bivalve culture and benthic ecosystems

Abstract: Coastal benthic ecosystems may be impacted by numerous human activities, including aquaculture, which continues to expand rapidly. Indeed, today aquaculture worldwide provides more biomass for human consumption than do wild fisheries. This rapid development raises questions about the interactions the practice has with the surrounding environment. In order to design strategies of sustainable ecosystem exploitation and marine spatial planning, a better understanding of coastal ecosystem functioning is needed so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 160 publications
(179 reference statements)
0
8
0
Order By: Relevance
“…These differences among estuaries suggest factors acting at large spatial scales may influence habitat linkages between oysters and surrounding sediments. This study showed the importance of habitat‐forming species in shaping the physicochemical and ecological characteristics in connected habitats at scale, adding to a growing body of literature on the ecosystem‐wide effects of habitat formers (e.g., Lacoste et al, 2020; van de Koppel et al, 2015). While previous studies have established how habitat interactions affect nutrient cycling around reefs (e.g., Hoellein & Zarnoch, 2014; Smyth, 2013), this is the first study to demonstrate relationships between proximity to reefs and sediment biodiversity.…”
Section: Discussionmentioning
confidence: 55%
“…These differences among estuaries suggest factors acting at large spatial scales may influence habitat linkages between oysters and surrounding sediments. This study showed the importance of habitat‐forming species in shaping the physicochemical and ecological characteristics in connected habitats at scale, adding to a growing body of literature on the ecosystem‐wide effects of habitat formers (e.g., Lacoste et al, 2020; van de Koppel et al, 2015). While previous studies have established how habitat interactions affect nutrient cycling around reefs (e.g., Hoellein & Zarnoch, 2014; Smyth, 2013), this is the first study to demonstrate relationships between proximity to reefs and sediment biodiversity.…”
Section: Discussionmentioning
confidence: 55%
“…To make this possible, it is necessary to actively support sustainable bivalve shellfish farming as part of cultural heritage and traditional value, and, at the same time, do an inventory of the biodiversity components, and monitor periodically the status of the marine environment (Golec and ECOSS Partnership, 2020). Indeed, aquaculture may impact the benthic habitats by increasing biodeposition to the seafloor (by mussel feces and pseudofeces) and induce variation in nutrient loading and fluxes, anaerobic metabolism in sediments and change in benthic community structure and functioning (Lacoste et al, 2020). In addition, the ecosystem in Malostonski zaljev N2K site is under the influence of the mainland, thus the surrounding land-based activities must be regulated to reduce water pollution and physical destruction of habitats due to urbanization.…”
Section: Management Aspects and Target Speciesmentioning
confidence: 99%
“…Although aquaculture is principally concerned with the production of food (food security) it can be designed to meet other societal challenges such as climate change mitigation (Sondak et al, 2017), adaption (Galappaththi et al, 2020), economic and social development (Ponte et al, 2014), and the mitigation of environmental and biodiversity degradation (Lacoste et al, 2020).…”
Section: Nbs Effectively Address Societal Challengesmentioning
confidence: 99%